Activities of Digital Platforms on the Basis of Clusterization and Innovative Development Strategies in the Conditions of European Integration - Babukh, Ilona; Kraus, Nataliia; Kateryna, Kraus; Lisitsa, Viktoriia; Novikova, Olha (My University, 2023)
The purpose of the scientific research is to present the features of the work of digital platforms based on clustering as a foundation on which the gradual formation of smart production and industry is built and to find ways to implement the innovative development strategy of Ukraine in the war and post-war times through the prism of digitalization. The object of scientific research is the digitization of the work of platforms, and the expansion of digital capabilities of their work due to the clustering and network interaction of business entities of the Industry 4.0 ecosystem as one of the key reserves of innovative development in the conditions of European integration. Authors’ opinion is: features of platform business models are presented, including: realtime, immediacy, spatiality, financial, and economic components; the features affecting the clustering processes of digital platforms are named, namely: mobility, Internet connectivity, artificial intelligence, gamification, ubiquitous computerization, ecosystemicity, networking. The peculiarities of digital transformation in the formation of enterprises of the Industry 4.0 ecosystem are revealed. The best global practices of digitization of production and industry and tools for improving the policy of innovation and digital development of the countries of the European Union are analyzed. Value/originality: having conducted a thorough analysis in parts of the acceleration of clustering of digital platforms, the authors proposed to apply in practice solutions such as the distribution of roles in accordance with real capabilities; gradual, integrative rapprochement; a single information field, regular communications; focus on quick wins; full integration with national initiatives. To speed up clustering based on digital platforms in Ukraine, it is proposed to include and profile already existing and verified Industry 4.0 Strategy projects. Conclusions. Clusters and participants of the ecosystem, which have export and internationalization experience, have been identified, which in the future could affect the quality of the implementation of Ukraine’s innovative development strategy in the context of European integration.
Keywords: digital platforms; clustering, clusters; innovative development strategy; European integration; automation of business processes; regional projects; internationalization; reserves of economic growth